Cloud based models in determination of solar radiation: A review - Ayu Wazira, Azhari; Kamaruzzaman, Sopian; Abdul Haqi, Ibrahim (World Scientific and Engineering Academy and Society, 2011)
The 3rd WSEAS International Conference on Renewable Energy Source (RES '09), 1st - 3rd July 2009 was held at University of La Laguna, Tenerife, Canary Island, Spain.